Maximising farm profitability through entrepreneurship development and farmers’ innovations: Feasibility analysis and action interventions - NAIN, M S; SINGH, RASHMI; MISHRA, J R; SHARMA, J P; SINGH, ANIL KUMAR; KUMAR, ANJANI; GILLS, RESHMA; SUMAN, R S (The Indian Journal of Agricultural Sciences, 2019)
The focus of capacity building has been shifting from primarily production to agri-business, based on market-led integration and developing other value chains aiming at enhancing farmers’ income. It requires identification and supporting of rural enterprises through technology and skill training, entrepreneurship training, market information, access to institutionalized credit, and other infrastructure related facilities.The need for appreciation of farmers as actors in the innovation system, and institutionalization of farmers’ wisdom for their scalability has been realized at most levels. To develop farming as a business venture and to integrate the farmers’ innovations and opportunities in secondary agriculture an action research study has been conducted in National Capital region of India. Institutional arrangement for facilitation of networking among stakeholders and resources was opined as the foremost requirement for enhancing farm income. The skills in social processes of group management and enterprise management were found lacking among the farmers. The entrepreneurial and technical trainings led to income generating activities. The price spread in major commercial crops showed that the longer chain reduced the producers’ share in consumer rupee drastically which implies the production linkages need to be developed with involvement of all the stakeholders. Through the lessons and opinion of respondents, maximizing farm profitability was found to be interplay of entrepreneurial competencies, entrepreneurial climate, and farmers’ innovations which suggest convergence and synergistic linkages.